Digging deeper evidence on the effects of macroprudential policies from a new database - Alam, Zohair (IMF working paper ;, 2019)
"This paper introduces a new comprehensive database of macroprudential policies, which combines information from various sources and covers 134 countries from January 1990 to December 2016. Using these data, the authors first confirm that loan-targeted instruments have a significant impact on household credit, and a milder, dampening effect on consumption. Next, they exploit novel numerical information on loan-to-value (LTV) limits using a propensityscore-based method to address endogeneity concerns. The results point to economically significant and nonlinear effects, with a declining impact for larger tightening measures. Moreover, the initial LTV level appears to matter; when LTV limits are already tight, the effects of additional tightening on credit is dampened while those on consumption are strengthened."--Abstract